Melahirkan Generasi Berkarakter Unggul melalui Transformasi Sosial yang Berbasis Pendidikan, Nilai, dan Kolaborasi Masyarakat di MTs Miftahul Khoir Alastengah Besuk - Muhammad Helmi; Ainur Rofiq Sofa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the efforts of MTs Miftahul Khoir Alastengah Besuk in fostering a generation of excellent character through social transformation based on education, religious values, and collaboration with the community. The main focus of this research is to explore how the school integrates moral and social values into its education to shape students' character, ensuring they are not only academically competent but also disciplined, responsible, and capable of working together. The research method used is a qualitative approach, with data collection techniques including interviews, observations, and documentation. The findings show that education at MTs Miftahul Khoir focuses not only on academic teaching but also on character development through active involvement of parents and the community. This collaboration is reflected in various social activities and community service programs, which provide students with opportunities to develop social skills and strengthen their relationships with the surrounding environment. In conclusion, the social transformation at MTs Miftahul Khoir successfully creates a generation that is not only academically intelligent but also possesses strong character and is ready to contribute positively to society. This study highlights the importance of synergy between formal education, local values, and community collaboration in creating an educational ecosystem that supports students' overall development.